Sustainable University - Lorber, Lučka (Journal for Geography, 2011)
This paper will discuss perceptions and understanding of sustainable development in the European University Area. Until recently, the main aspect to be considered and analysed has been the aspect of sustainability in education and learning within higher-education programmes as a need of forming a culture of ecological awareness and of human responsibility towards the environment. Nowadays, the awareness of sustainable development circles in different directions; it comprises the entire research- and educational higher-education activity and affects the interest networking in society. It also directs the university development and sustainable culture strategy and policy as well as understanding the integrity of the university area. Contemplating the future of the University of Maribor on a basis of sustainability sees its essence in the conscious responsibility for changes which includes the entire science system and all educational forms/types along with human ethical behaviour for achieving ecological and social justice.
Keywords: university development; higher-education activity; sustainable ethics; ethics; global justice; University of Maribor